Shot Peening Effects on Subsurface Layer Properties and Fatigue Performance of Case-Hardened 18CrNiMo7-6 Steel - H. S. Ho; D. L. Li; E. L. Zhang; P. H. Niu (Advances in Materials Science and Engineering)
The present study is conducted with a dual-aim: firstly, to examine the effect of several single shot peening conditions on the subsurface layer properties and fatigue performance of the case-hardened 18CrNiMo7-6 steel, and secondly, to propose an optimized peening condition for improved fatigue performance. By carrying out the subsurface integrity analysis and fatigue testing, the underlying relationships among the peening process, subsurface layer property and fatigue performance are investigated, the way peening conditions affect the fatigue life and its associated scatter for the case-hardened 18CrNiMo7-6 steel is quantitatively assessed. The in-depth study shows that dual peening can be an optimized solution, for it is able to produce a subsurface layer with enhanced properties and eventually gain a significant improvement in fatigue performance.